Returns from Concentration Camps - Halamová, Martina (Poznańskie Studia Slawistyczne, 2017)
The article is concentrated on the Czech post-war literature, especially on the Czech treatment of the theme regarding returns from concentration camps in the novels written in the second half of 20th century and in contemporary literature. The presented novels, thematizing the mentioned topic, are viewed as representations of those days discourses shaped by the “course of history”. Therefore, the article follows variation of the theme as well as the modification of heros in connection with the transformation of discourses, and tries to describe the reasons of the changing.